The comparative cardiovascular and renal effectiveness of sodium‐glucose co‐transporter‐2 inhibitors and glucagon‐like peptide‐1 receptor agonists: A Scandinavian cohort study. Issue 3 (24th November 2021) - Ueda, Peter; Wintzell, Viktor; Dahlqwist, Elisabeth; Eliasson, Björn; Svensson, Ann‐Marie; Franzén, Stefan; Gudbjörnsdottir, Soffia; Hveem, Kristian; Jonasson, Christian; Melbye, Mads; Hviid, Anders; Svanström, Henrik; et al.
Abstract: Aim: To assess the comparative cardiovascular and renal effectiveness of sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors versus glucagon‐like peptide‐1 (GLP‐1) receptor agonists in routine clinical practice. Materials and Methods: A cohort study of nationwide registers from Sweden, Denmark, and Norway, including 87 525 new users of SGLT2 inhibitors and 63 921 new users of GLP‐1 receptor agonists, was conducted using data from 2013‐2018. Co‐primary outcomes, analysed using an intention‐to‐treat exposure definition, were major adverse cardiovascular events (MACE; myocardial infarction, stroke, and cardiovascular death), heart failure (hospitalization or death because of heart failure), and serious renal events (renal replacement therapy, hospitalization for renal events, and death from renal causes). Results: Use of SGLT2 inhibitors versus GLP‐1 receptor agonists was associated with a higher risk of MACE (adjusted incidence rate: 15.2 vs. 14.4 events per 1000 person‐years; HR 1.07 [95% CI 1.01‐1.15]), a similar risk of heart failure (6.0 vs. 6.0 events per 1000 person‐years; HR 1.02 [0.92‐1.12]), and a lower risk of serious renal events (2.9 vs. 4.0 events per 1000 person‐years; HR 0.76 [0.66‐0.87]). In as‐treated analyses, the HR (95% CI) was 1.11 (1.00‐1.24) for MACE, 0.88 (0.74‐1.04) for heart failure, and 0.60 (0.47‐0.77) for serious renal events. In secondary outcome analyses, use of SGLT2 inhibitors versus GLP‐1 receptor agonists was not associated with statistically significant differences for the risk of myocardial infarction (HR 1.09 [95% CI 1.00‐1.19]), cardiovascular death (HR 0.97 [95% CI 0.84‐1.12]), death from renal causes (HR 0.75 [95% CI 0.41‐1.35]), or any cause death (HR 1.01 [95% CI 0.94‐1.09]), while the risk of stroke was higher (HR 1.14 [95% CI 1.03‐1.26]), and the risk of renal replacement therapy (HR 0.74 [95% CI 0.56‐0.97]) and hospitalization for renal events (HR 0.75 [95% CI 0.65‐0.88]) were lower among users of SGLT2 inhibitors. Conclusions: Use of SGLT2 inhibitors versus GLP‐1 receptor agonists was associated with a similar risk of heart failure and a lower risk of serious renal events, while use of GLP‐1 receptor agonists versus SGLT2 inhibitors was associated with a slightly lower risk of MACE. In as‐treated analyses, the associations with MACE and serious renal events increased in magnitude, and the HR for heart failure tended towards a protective association for SGLT2 inhibitors.